2022
DOI: 10.1021/acs.macromol.2c00425
|View full text |Cite
|
Sign up to set email alerts
|

Photocured Simultaneous and Sequential PDMS/PMMA Interpenetrating Polymer Networks

Abstract: Photocured interpenetrating polymer networks (IPNs) of PDMS and PMMA were synthesized through a sequential route to form semi-IPNs and a simultaneous route to form graft IPNs. Experiments were designed to understand the effect of network architecture and PMMA concentration on IPN microstructure, thermal properties, mechanical properties, and chemical structure. At PMMA concentrations above 10 wt %, the microstructure in both IPN architectures consisted of a dispersed PMMA phase in a PDMS continuous phase, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 48 publications
(75 reference statements)
2
26
0
Order By: Relevance
“…These spherical domains have characteristic length scales on the order of 50–100 nm. While there is significant mechanical contrast observed between these domains, there still exists a degree of PDMS/PMMA mixing in both phases, as investigated in our prior work . The PDMS/PIBoMA graft-IPN in Figure b shows a qualitatively different morphology than that of the PDMS/PMMA material, with significantly smaller domain sizes and a lower degree of phase contrast between the PIBoMA-rich domains and the underlying matrix.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These spherical domains have characteristic length scales on the order of 50–100 nm. While there is significant mechanical contrast observed between these domains, there still exists a degree of PDMS/PMMA mixing in both phases, as investigated in our prior work . The PDMS/PIBoMA graft-IPN in Figure b shows a qualitatively different morphology than that of the PDMS/PMMA material, with significantly smaller domain sizes and a lower degree of phase contrast between the PIBoMA-rich domains and the underlying matrix.…”
Section: Resultssupporting
confidence: 91%
“…This understanding of the AFM phase data has been supported by the elemental contrast seen in electron microscope images, as reported in our previous work on PDMS/PMMA IPNs. 10 A constant phase angle range was used in the three images to highlight quantitative differences in phase contrast between the images. An inset where the phase angle range was reduced has also been added to the PDMS/PIBoMA graft-IPN image in Figure 2b to highlight local differences in tip−sample energy dissipation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, we also investigated mixing in IPNs using dynamic mechanical thermal analysis (DMTA) for PDMS/PMMA IPNs with different synthesis routes and compositions. IPNs exhibited either a broad tan-delta peak in the PMMA glass transition range, suggesting that all dispersed domains consist of a mixture of PDMS and PMMA, or two peaks, suggesting that some domains are a mixture and others are pure PMMA . These studies provide a macroscopic perspective by averaging over a large sample volume, but there is minimal information at the local nanoscale level.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] In another recent example, Beebe and coworkers demonstrated that semi‐IPNs (e.g., one cross‐linked and one uncross‐linked network) prepared from sequential polymerization of poly(siloxanes) and poly(methyl methacrylate) were better mixed than the chemically identical IPNs prepared using simultaneous polymerizations, which enabled moduli tunability of 2.5× (i.e., 20–50 MPa). [ 25,26 ] In these examples, the reliance on a single stimulus for initiation (e.g., light or heat, respectively) precluded the ability to spatially control morphology.…”
Section: Introductionmentioning
confidence: 99%